2023
DOI: 10.1002/arch.22048
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of a NPC1 gene from the whitefly, Bemisia tabaci (Hemiptera: Aleyrodidae)

Hao Yu,
Liuhao Wang,
Shunxiao Liu
et al.

Abstract: Niemann‐Pick C (NPC) disease is a neurodegenerative disorder related to cellular sterol trafficking and mutation of NPC1 gene is the main cause for this disease. The function of NPC1 have been reported in a few insects but rarely studied in hemipterans. In the present study, we investigate the function of NPC1 in a hemipteran pest, the whitefly Bemisia tabaci. It was found that B. tabaci had only one NPC1 homolog (BtNPC1), in contrast to two homologs in many other insects. BtNPC1 was ubiquitously expressed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Two homologous NPC1s ( NPC1a and NPC1b ) have been reported in H. sapiens , Mus musculus and D. melanogaster , and were found to be responsible for dietary cholesterol absorption and intracellular cholesterol transport, respectively [ 31 ]. However, other insects, such as B. tabacis , have been reported to only have NPC1, which may be involved in both of the above-mentioned physiological processes [ 24 ]. In this study, only one NPC1 homolog was found in M. nipponense , which exhibited three typical conserved domains of the NPC family (NPC1_N, SSD, and PTC).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Two homologous NPC1s ( NPC1a and NPC1b ) have been reported in H. sapiens , Mus musculus and D. melanogaster , and were found to be responsible for dietary cholesterol absorption and intracellular cholesterol transport, respectively [ 31 ]. However, other insects, such as B. tabacis , have been reported to only have NPC1, which may be involved in both of the above-mentioned physiological processes [ 24 ]. In this study, only one NPC1 homolog was found in M. nipponense , which exhibited three typical conserved domains of the NPC family (NPC1_N, SSD, and PTC).…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila spp., NPC1a had a wide tissue distribution, while NPC1b was only expressed in the midgut epithelial cells [ 31 ]. The highest expression of NPC1 in B. mori was found in the testes, while, in B. tabaci , it was in the abdomen [ 24 ]. These results suggest that NPC1 may play different crucial physiological roles in different species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations